Pengaruh Pengendalian Intern, Kepatuhan Dan Kompensasi Manajemen Terhadap Perilaku Etis Karyawan Pada LPD Karangasem Bali - Merta I Ketut; Sudiasa I Komang; Yusnimi Ni Made (Departement of Mathematics Education, 2024)
This research takes as its object the Village Credit Institution (LPD) in Karangasem. The aim is to test the influence of internal control, compliance and management compensation on employee ethical behavior using grand theory. Stewardship (Daviset al, 1997).Quantitative Multiple Regression Research Method with a sample of 108 and data analysis using SPSS Version 24.Research Results (1) Internal Control (X1) has a positive and significant effect on the Ethical Behavior of Village Credit Institution Employees in Karangasem Bali, (2) Compliance (X2) has a positive and significant effect on the Ethical Behavior of Village Credit Institution Employees in Karangasem Bali, (3) Management Compensation (X3) has a positive and significant influence on the Ethical Behavior of Village Credit Institution Employees in Karangasem Bali, (4) Employee Ethical Behavior (Y) has a positive and significant influence simultaneously on Internal Control, Compliance, Management Compensation so that it becomes one unit in the Village Credit Institution in Karangasem Bali Research Implications This research found that the influence of the variables Internal Control, Compliance, Management Compensation on the Ethical Behavior of Village Credit Institution Employees in Karangasem is very large